Philosophical roots of Quaternary Prevention - Daniel Widmer (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
This article explores two philosophical dimensions of quaternary prevention since it represents the family doctors' response to overmedicalization. The first dimension refers to the theory of knowledge and the second to the theory of action. Despite their interconnectedness, they are addressed separately. Firstly, in the theories of knowledge (Epistemology) we argue that the positivism of Evidence-Based Medicine (EBM), so useful to select good practices, should be balanced against critical vision of the use of EBM coupled with a constructivist view through the narrative-based medicine. Secondly, in the theory of action (Ethics) we argue that the non-maleficence principle (primum non nocere) needs to be balanced by the beneficence principle. The latter is the primary medical obligation and doctors should cultivate this practical wisdom. Finally, some aspects of P4's future challenges are discussed such as health inequalities, interprofessional collaboration, responsibility, managerialism, and the integrative medicine, where a philosophical position should be considered.